The role of microglial exosomes in brain injury - Chen, Yahong; Zhu, Jie; Ji, Jingjing; Liu, Zhifeng; Ren, Guangli (Frontiers in Cellular Neuroscience, 2022)
Microglia are involved in immune responses to central nervous system (CNS) injury. Meanwhile, exosomes derived from microglia are important mediators of information and material exchange in brain, which play an important role in neuroprotective or damaging effects. Microglial exosomes contain a variety of molecular cargos, including microRNAs, soluble proteins, and lipids, which have regulatory effects on other types of cells and microenvironment in brain. In this review, we summarized microglial exosome characteristics, release patterns, pro-proliferative and pro-apoptotic effects on neurons and other glial cells, immunomodulatory effects, and regulation of the extracellular microenvironment. Understanding the relationship between microglia exosomes and brain injury can provide new targets for clinical treatment.